UNIVERSITY ATTRITION IN STUDENTS FROM A PRIVATE UNIVERSITY IN IQUITOS - Mori Sánchez, Maria del Pilar (2012)
University attrition is a complex problem which may include different variables. This article seeks to describe the reasons behind university attrition in a private university in the city of Iquitos. The sample included 88 young people who dropped out the studies at University where the present study was carried out, whose ages range between 18-25 years, from which 42% are women and 58% males. The data from focus group was analyzed, as well as the interviews and the systematization of the existing information. The results show that the institutional characteristics would be the first factor that triggers attrition, followed by the vocational interests, academics, and finally the economic factor.